2019
DOI: 10.1101/870451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rif1 functions in a tissue-specific manner to control replication timing through its PP1-binding motif

Abstract: 22Replication initiation in eukaryotic cells occurs asynchronously throughout S phase, yielding early 23 and late replicating regions of the genome, a process known as replication timing (RT). RT changes 24 during development to ensure accurate genome duplication and maintain genome stability. To 25 understand the relative contributions that cell lineage, cell cycle, and replication initiation 26 regulators have on RT, we utilized the powerful developmental systems available in Drosophila 27 melanogaster. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…The high level of similarity is particularly noteworthy in the case of the early RT profiles, given that the flow sorting gate for early replicating nuclei in the endocycle had to be adjusted to minimize contamination from late replicating mitotic nuclei ( Fig 1C ). This overall conservation of the RT program in the endocycle is consistent with a recent study in Drosophila follicle cells which found no regions of differential RT between mitotic and endocycling cells [ 78 ]. Additionally, the global maintenance of RT in the two types of cell cycles in maize roots suggests that the process of re-establishing the RT program must be similar in both.…”
Section: Discussionsupporting
confidence: 91%
“…The high level of similarity is particularly noteworthy in the case of the early RT profiles, given that the flow sorting gate for early replicating nuclei in the endocycle had to be adjusted to minimize contamination from late replicating mitotic nuclei ( Fig 1C ). This overall conservation of the RT program in the endocycle is consistent with a recent study in Drosophila follicle cells which found no regions of differential RT between mitotic and endocycling cells [ 78 ]. Additionally, the global maintenance of RT in the two types of cell cycles in maize roots suggests that the process of re-establishing the RT program must be similar in both.…”
Section: Discussionsupporting
confidence: 91%
“…Late in the S phase, higher CDK—and likely DDK—concentration causes Rif1 inhibition, which results in origin derepression through pre-RC activation [ 31 ]. For polytene chromosomes, the influence of Rif1 on replication timing has been analyzed in detail only for the annotated part of the genome: euchromatin arms and the part of heterochromatin devoid of satellite DNA [ 27 , 65 ]. It has been concluded that Rif1 action is SUUR-dependent and is implemented through the impact on the speed or stability of replication forks [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate the existence of at least two mechanisms of Rif1 action, both requiring the interaction of Rif1 with PP1 phosphatase [ 27 , 31 ]. Of note, a mutation in the Rif1 gene has an opposite effect on some eu- and heterochromatin regions [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations